Using VLF Transmitter Signals at LEO for Plasmasphere Model Validation. Issue 4 (7th April 2022) - Usanova, M. E.; Reid, R. A.; Xu, W.; Marshall, R. A.; Starks, M. J.; Wilson, G. R.
Abstract: This study presents analysis of very low frequency (VLF) transmitter signal measurements on the Very‐Low‐Frequency Propagation Mapper (VPM) CubeSat in low‐Earth orbit. Six months of satellite operation provided good data coverage, used to build global statistical maps of VLF power distribution. The power distribution above four powerful transmitters is used as input for ray tracing to study signal propagation to the conjugate hemisphere in two plasmaspheric density models. The ray tracing results are further compared with VPM measurements to determine which model provides better agreement with observations. As ray propagation largely depends on the background plasma density distribution, this indirect method can be used for plasmaspheric density model validation as an alternative to multipoint in situ plasma measurements that may not be readily obtainable. In addition, it can be used to investigate Landau damping and ducted versus non‐ducted propagation of VLF signals. Plain Language Summary: Very low frequency (VLF) transmitter signals at frequencies in the tens of kHz, used for military communication with submerged submarines, can be used to determine the plasma density distribution in near‐Earth space. Here we demonstrate how a combination of VLF antenna measurements from low‐Earth orbit and numerical modeling of VLF signal propagation can be applied to constrain plasma density profiles in the magnetosphere. This is an indirect method that can be used for plasmaspheric density model validation as an alternative to multipoint in situ plasma measurements that may not be readily obtainable. Key Points: At L < 3, the Diffusive Equilibrium plasmasphere model provides much better agreement with observations than the Global Core Plasma Model Signals from selected transmitters at L = 1.17–2.87 propagate primarily in a non‐ducted mode Landau damping is insignificant for the selected transmitters